Planum Sphenoidale Meningioma: A Rare Location of Skull Base Meningioma - Sinaga, Patrice LWY; Faisal; Dharmajaya, Ridha (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Background: Meningioma is common primary central nervous system tumors. Twenty-five percent of all meningioma consist of skull base meningioma. Planum sphenoidale meningiomas are rare. Planum sphenoidale meningiomas can extend into adjacent areas. Approximately two thirds of patients complain of failing vision in one eye as the first symptom. Case Report: A 32-year-old woman presented with 6-month history of progressively worsening blurred of both of vision. She also complained her smell ability was reduced for 3 months. She had headache for 6 months. The pain was worsening in the morning. She is conscious. A neurologic examination revealed bilateral hyposmia and visual deficits but no weakness. Visus of oculo dextra was 1/300 and visus of oculo sinistra was no light perception. Magnetic resonance imaging (MRI) intravena contrast of brain revealed a large extra-axial mass measured Â±6,2x5,9x6 cm centred on planum sphenoidale displacing both frontal lobes. She had an operation of tumor removal with cranio-orbito-zygotomy approach. The tumor, which measured Â±7cmx7cmx6 cm, was succesfully removed completely. She gets improvement of smell ability and both visual postoperatively. The histopathology of the tumor revealed meningioma WHO grade I. Discussion: Planum sphenoidale meningiomas present a frequently encountered pathology of the anterior skull base. These meningiomas give rise to an early visual disturbance with relatively slow progression. Displacement of the olfactory tracts and optic chiasm occur when the meningioma extends into the paranasal sinuses and nasal cavity. Clinical presentation and diagnosis often occur in the late stage. Anosmia is one of common finding on physical examination. Postoperative improvement of visual symptoms depends on the preoperative duration of those symptoms.